Effect of Commercially Available Plant-Derived Essential Oil Products on Arthropod Pests - Cloyd, Raymond A; Galle, Cindy L; Keith, Stephen R; Kalscheur, Nanette A; Kemp, Kenneth E (Journal of economic entomology, 2009)
Plant-derived essential oil products, in general, are considered minimum-risk pesticides and are exempt from Environmental Protection Agency registration under section 25 (b) of the Federal Insecticide Fungicide and Rodenticide Act. However, many of the plant-derived essential products available to consumers (homeowners) have not been judiciously evaluated for both efficacy and plant safety. In fact, numerous plant-derived essential oil products labeled for control of arthropod pests have not been subject to rigorous evaluation, and there is minimal scientific information or supporting data associated with efficacy against arthropod pests. We conducted a series of greenhouse experiments to determine the efficacy and phytotoxicity of an array of plant-derived essential oil products available to consumers on arthropod pests including the citrus mealybug, Planococcus citri (Risso); western flower thrips, Frankliniella occidentalis (Pergande); twospotted spider mite, Tetranychus urticae Koch; sweetpotato whitefly B-biotype, Bemisia tabaci (Gennadius); and green peach aphid, Myzus persicae (Sulzer). Although the products Flower Pharm (cottonseed, cinnamon, and rosemary oil) and Indoor Pharm (soybean, rosemary, and lavender oil) provided >90% mortality of citrus mealybug, they were also the most phytotoxic to the coleus, Solenostemon scutellarioides (L.) Codd, plants. Both GC-Mite (cottonseed, clove, and garlic oil) and Bugzyme (citric acid) were most effective against the twospotted spider mite (>=90% 0ortality). However, SMC (canola, coriander oil, and triethanolamine), neem (clarified hydrophobic extract of neem oil), and Bug Assassin (eugenol, sodium lauryl sulfate, peppermint, and citronella oil) provided >80% mortality. Monterey Garden Insect Spray, which contained 0.5% spinosad, was most effective against western flower thrips with 100% mortality. All the other products evaluated failed to provide sufficient control of western flower thrips with <30% mortality. In addition, the products Pest Out (cottonseed, clove, and garlic oil), Bang (Pipereaceae), and Fruit & Vegetable Insect Spray (rosemary, cinnamon, clove oil, and garlic extract) had the highest flower (transvaal daisy, Gerbera jamesonii [H. Bolus ex Hook.f]) phytotoxicity ratings (>=4.5 of 5) among all the products. None of the plant-derived essential oil products provided sufficient control of sweetpotato whitefly B-biotype or green peach aphid 7, 14, and 21 d after application. Furthermore, the products Bug Assassin (eugenol, sodium lauryl sulfate, peppermint, and citronella oil) and Sharpshooter (sodium lauryl sulfate and clove oil) were phytotoxic to the poinsettia, Euphorbia pulcherrima Willd. ex Klotzsch, plants. This study is one of the first to quantitatively demonstrate that commercially available plant-derived essential oil products vary in their effectiveness against certain arthropod pests stated on the label and are phytotoxic.